Cardioprotective Role of Flavokawain A against Isoproterenol-Induced Acute Myocardial Infarction in Rats via Modulation of NF-?B/HO-1/NQO-1 Pathways - Wu, Li; Qin, Feizhang; Zhao, Chengcheng; Hou, Ping (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Myocardial Infarction (MI) is a prevalent condition of heart disease. Despite remarkable growth in the treatment of heart diseases, MI remains the foremost cause of mortality worldwide and a significant pathological concern. Objectives The primary aim of this work is to analyze the therapeutic activities of flavokawain A on Isoproterenol (ISO)-induced MI in rats. Materials and Methods The rats were administered with ISO (85 mg/kg) in order to induce MI and pretreated with flavokawain A. The heart and body weights of all rats were measured. An analysis was conducted on the levels of uric acid, CRP and total protein. The cardiac function marker enzymes and antioxidant levels were studied using kits. The Na+/K+, Mg2+ activities and Ca2+ ATPase, Na+, K+ and Ca2+ ions, as well as the inflammatory markers and NF-κB and HO-1/ NQO-1 protein levels, were examined using corresponding kits. Heart samples were subjected to histopathological examination to identify histological alterations. Results Conclusion The treatment of flavokawain A significantly enhanced the levels of antioxidants and the Na+/K+, Mg2+ and Ca2+ ATPase enzymes. Additionally, it effectively diminished the inflammatory marker levels and controlled cardiac enzyme activities. Therefore, it has the potential to be an effective treatment option in the future for treating MI.
Keywords: Myocardial infarction; Flavokawain A; Inflammation; Ca2+ ATPase; Antioxidants.